Methodological foundations for developing research competencies of prospective physics teachers through the example of X-ray diffraction - Dalabayev, Tleubek; Nurizinova, Makpal; Skakov, Mazhyn; Coruh Аli (International Journal of Innovative Research and Scientific Studies, 2025)
Research competence is a key component in the professional preparation of future physics teachers, as it directly contributes to their ability to integrate scientific inquiry into teaching practice. This study aims to design and validate a methodological framework that strengthens research skills within the context of STEM education, using X-ray diffraction as a central phenomenon for instruction. The research employs innovative STEM-oriented pedagogical approaches that emphasize inquiry-based learning, interdisciplinary integration, and the application of information and communication technologies (ICT). A large-scale educational experiment was conducted across two universities, involving 148 undergraduate and graduate students, 50 university faculty members, and 43 secondary schools in two regions. Data were collected through surveys, diagnostic assessments, and structured evaluations to measure the quality of student learning outcomes. Based on the findings, an elective course on X-ray diffraction was developed, accompanied by comprehensive teaching materials and an electronic training manual. The implementation of this elective resulted in a 22.5% increase in students’ educational performance, thereby confirming the effectiveness of the proposed methodology. The results suggest that integrating STEM-based elective courses grounded in specialized scientific phenomena not only enhances the research competencies of prospective physics teachers but also contributes to raising the overall quality of physics education in higher education institutions.